Unitarian Church, Belfast, ME - Auteur inconnu (Wikimedia Commons, 1909)
Notice image issue de Wikimedia Commons. Titre: Unitarian Church, Belfast, ME. Unitarian Church, Belfast, ME | from a 1909 postcard. Known as the First Church, it was erected by master-builder Samuel French and dedicated on November 15, 1818.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; architecture; Histoire Locale; église; Carte postale